A search for point sources of EeV neutrons - Abreu, P.; Aglietta, M.; Ahlers, M.; Ahn, E. J.; Albuquerque, I. F. M.; Gomez Berisso, Mariano; Zhou, J.; Zhu, Y.; Zimbres Silva, M.; Ziolkowski, M. (IOP Publishing, 2012)
Fil: Abreu, P.. Technical University of Lisbon; Portugal